How eHealth use and cancer information-seeking influence older adults’ acceptance of genetic testing: Mediating roles of PIGI and cancer worry - Yinxia Zhu; Qian Erica Xiao; Man Chon Ao; Xinshu Zhao (Digital Health)
Objective This study aims to investigate how eHealth use and information-seeking behavior affect older adults’ acceptance of genetic testing, focusing on their participation in genetic tests and their willingness to adopt lifestyle changes based on test results. The research highlights the mediating roles of the perceived importance of genetic information (PIGI) and cancer worry. Methods This cross-sectional study used secondary data from the Health Information National Trends Survey (HINTS 5, Cycle 4), conducted in 2020. The analysis included 1852 adults aged 60 and above. Two mediation models were tested using SPSS 25. Model 1 examined the relationship between eHealth use, perceived importance of genetic information (PIGI), and genetic test behavior. Model 2 analyzed how cancer information-seeking influences willingness to change lifestyle behavior (WCLB) based on genetic test results, with cancer worry as a mediator. Results Both models showed statistically significant mediation effects ( p  < 0.05). Model 1 found that eHealth use positively influences genetic test behavior through PIGI. Model 2 revealed that cancer information-seeking indirectly impacts willingness to change lifestyle behavior (WCLB) based on the genetic test results via cancer worry, confirming a full mediation effect. Additionally, among demographic variables, educational level was the strongest predictor of genetic test behavior, while gender significantly predicted WCLB, with older female adults showing higher intentions to change their lifestyle based on genetic test results than males. Conclusion The study highlights the pivotal roles of PIGI and cancer worry in shaping older adults’ acceptance of genetic testing, encompassing both performing genetic test behaviors and adopting lifestyle changes based on test results. These findings offer actionable insights for designing targeted health communication strategies and interventions to enhance genetic testing uptake and foster proactive health management among older populations.